2022
DOI: 10.1063/5.0097114
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced noise sources and reduction methods in centrifugal pumps: A literature review

Abstract: The present review paper describes the research work conducted by many researchers in the field of hydro acoustics of centrifugal pumps. This study aims to understand the flow induced noise mechanism, factors affecting it, and available methods to attenuate the same in centrifugal pumps. In general, the noise generated by a pump is interpreted in terms of pressure pulsations and can be represented in the frequency domain as a combination of discrete components and broadband components. In the discrete frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Therefore, the internal field noise of two types of sound sources is superimposed on the corresponding frequency, and the superposition result is expressed by the total sound pressure level L p , to improve the reliability of noise numerical calculation. The superposition formula is defined in equation (2).…”
Section: Computational Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the internal field noise of two types of sound sources is superimposed on the corresponding frequency, and the superposition result is expressed by the total sound pressure level L p , to improve the reliability of noise numerical calculation. The superposition formula is defined in equation (2).…”
Section: Computational Model Validationmentioning
confidence: 99%
“…The volute is one of the main flow passage components of the centrifugal pump, so its structural parameters are directly related to pump performance. 2 Therefore, it is essential to improve efficiency and reduce noise by optimizing the volute structure.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have found that quasi-steady-state analysis is insufficient to accurately evaluate transient flows inside the pump (Zhang et al, 2013a, b). Some scholars have employed the particle displacement velocimetry to measure velocity distributions and investigate the influence of non-uniform outflow on pressure fluctuations and noise in the pump (Gangipamula et al, 2022;Luo et al, 2016). Others have designed testing methods and systems to study the transient characteristics of the inlet flow field during the start-up process of mixed-flow pumps, and have obtained velocity distributions during the start-up process with PIV techniques (Li et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…, 2013a, b). Some scholars have employed the particle displacement velocimetry to measure velocity distributions and investigate the influence of non-uniform outflow on pressure fluctuations and noise in the pump (Gangipamula et al. , 2022; Luo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Noise generated by rotating machinery could adversely affect the environment and creatures' health [1]. Since the flow-induced sound plays a crucial role in the pump noise and the vortex structures are considered vital factors in the turbulent flow [2], it is meaningful to investigate the influence of the vortex on the sound source generation.…”
Section: Introductionmentioning
confidence: 99%